Using Telemedicine to Pre-Screen Sports Medicine Patients in the Ambulatory Setting Reduces Wait Times and Maximizes Provider-Patient Interaction. Issue 7 (29th July 2019) - Atanda, Alfred; Leyden, Kathryn; Student, Medical
Objectives: Gathering of background information during a clinic visit can be time-consuming. Some medical specialties have workflows that pre-screen patients ahead of time to minimize delays. Having background information ahead of time may decrease delays and ensure that the visit is focused on physical examination, diagnosis, and treatment. We have used telemedicine to treat established patients to reduce cost and resource utilization, while maintaining high levels of patient satisfaction. It is conceivable that telemedicine could also be used to pre-screen new patients prior to their in-person clinic visit. The goal of the current study was to evaluate whether utilizing telemedicine to pre-screen new patients to our sports medicine clinic would reduce time in the exam room waiting and being seen, and overall clinic times. Methods: From June 2018 through August 2018, we utilized videoconferencing telemedicine to pre-screen all new patients to a pediatric sports medicine clinic with a chief diagnosis of knee pain. Visits were performed by full-time telemedicine pediatricians who were provided appropriate training and an intake form describing which questions should be asked. All visits utilized the American Well software platform (Boston, USA) and were performed on the patient's personal device. During the subsequent in-person visit, the overall timing of the visit was recorded including: time checked in, time waiting in waiting room, time waiting in exam room, time spent with provider, and time-checked out, were all recorded. Similar time points were recorded for matched control patients that did not undergo telemedicine pre-screening and were seen in the traditional manner. Inclusion criteria included: being brand new to the practice and unilateral knee pain. Results: There were eight pre-screened patients and ten control patients in this cohort. Compared to controls, pre-screened patients spent less time in the exam room (19 min vs. 31 min), higher percentage of the exam room time with the provider (58% vs. 34%), higher percentage of the overall visit time with the provider (29% vs. 19.5%), and less time for the overall visit (39 min vs. 52 min). Conclusion: Pre-screening patients to obtain background information can decrease exam room waiting time and overall visit time and maximize time during the visit spent with the provider. In addition, it could potentially be used to increase throughput through the clinic and improve patient satisfaction scores.